1997
DOI: 10.1006/cbir.1996.0126
|View full text |Cite
|
Sign up to set email alerts
|

Alzheimer's Soluble Amyloid Beta Protein Is Secreted by Hepg2 Cells as an Apolipoprotein

Abstract: Recently we reported that the soluble form of amyloid beta protein (sA beta) in normal human plasma and cerebrospinal fluid is associated with lipoprotein (LP) particles. In this paper we tested the sA beta secretion by cells in association with LP in the model of the human hepatoma HepG2 cell line. These cells secreted sA beta to the culture media and expressed intracellular sA beta immunoreactivity. Soluble A beta in the cell supernatant was detected in 200-300 kDa LP complexes in association with apoA-I, ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 31 publications
2
24
0
Order By: Relevance
“…In blood, signiWcant A is associated the triglyceriderich lipoproteins (TRLs) (Mamo et al 2008) consistent with the Wndings by Koudinov and Koudinova (1997), who found that hepatocytes secrete A exclusively as a lipoprotein complex. In recent studies, we reported that the absorptive epithelial cells of the small intestine (enterocytes) have substantial abundance of A , secreted into blood associated with dietary induced lipoproteins (chylomicrons) (Galloway et al 2007).…”
Section: Introductionsupporting
confidence: 53%
“…In blood, signiWcant A is associated the triglyceriderich lipoproteins (TRLs) (Mamo et al 2008) consistent with the Wndings by Koudinov and Koudinova (1997), who found that hepatocytes secrete A exclusively as a lipoprotein complex. In recent studies, we reported that the absorptive epithelial cells of the small intestine (enterocytes) have substantial abundance of A , secreted into blood associated with dietary induced lipoproteins (chylomicrons) (Galloway et al 2007).…”
Section: Introductionsupporting
confidence: 53%
“…It remains indeterminate whether Ab is present in biological fluids as a part of a lipoprotein complex under stress conditions. Existence of such acute-phase Ab-lipoprotein complexes can be postulated taking into account consistent data on the association between Ab and HDL-like lipoproteins under normal conditions [11][12][13][14]. As described above, secreted Ab might be associated with a subset of small, dense, HDL-like lipoproteins.…”
Section: Monomeric Ab Protects Against Oxidative Stressmentioning
confidence: 86%
“…Similarly, monomeric Ab co-isolates with lipoprotein particles from human plasma, in particular with the HDL and very high density lipoprotein (VHDL) fractions [12], and from AD brains [13]. Finally, human hepatoma HepG2 cells secrete Ab in the culture medium as a part of 200-300 kDa lipoprotein complexes in association with apolipoprotein (apo) A-I, apoJ, phospholipids, triglycerides and free and esterified cholesterol [14].…”
Section: Ab Is Associated With Lipoproteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Koudinov et al [11] reported that hepatocytes secrete amyloid-β as a lipoprotein complex. Another organ where it has been documented that Aβ is produced is the small intestine.…”
Section: Findings On Amyloid-β Production Induced By Saturated Fat DImentioning
confidence: 99%